Physics Olympiad : Basic to Advanced Exercises - Committee of Japan Physics Olympiad (Singapore ; World Scientific Pub. Co., 2014)
This book contains some of the problems and solutions in the past domestic theoretical and experimental competitions in Japan for the International Physics Olympiad. Through the exercises, we aim at introducing the appeal and interest of modern physics to high-school students. In particular, the problems for the second-round of competition are like long journey of physics, beginning with fundamental physics of junior-high-school level, and ending with the forefronts of updated physics and technology.
ch. 1. General physics. Elementary problems. Advanced problems -- ch. 2. Mechanics. 2.1. Motion with a constant acceleration. 2.2. Equation of motion. 2.3. The law of conservation of energy. 2.4. Newton's law of universal gravitation. 2.5. Conservation of momentum. 2.6. Moment of force and angular momentum. 2.7. The Keplerian motion. 2.8. Motion and energy of rigid bodies -- ch. 3. Oscillations and waves. 3.1. Simple harmonic oscillation. 3.2. Waves. 3.3. Superposition of waves. 3.4. The Doppler effect -- ch. 4. Electromagnetism. 4.1. Direct-current circuits. 4.2. Magnetic field and electromagnetic induction. 4.3. Electric charge and electric field. 4.4. Current and magnetic field -- ch. 5. Thermodynamics. 5.1. Heat and temperature. 5.2. Kinetic theory of gases. 5.3. The first law of thermodynamics -- ch. 6. Modern physics. Elementary problems. Advanced problems. Discovery of a strange star, white dwarf. Particle motion in a very small scale - Heisenberg uncertainty principle. A new type of coordinate, phase space. Degenerate state of electrons. Degenerate pressure of electrons. Relativistic and non-relativistic kinetic energy. Degenerate pressure in the three-dimensional space. Fate of the sun. Gravitational energy of a star. Evolution of stars. Chandrasekhar mass. Black hole -- ch. 7. How to measure and analyze data. 7.1. Some hints for experiments. 7.2. Measurement errors and significant figures. 7.3. Statistical errors. 7.4. Errors in indirect measurements and error propagation. 7.5. Best-fit to a linear function. 7.6. Best-fit to a logarithmic function. 7.7. Summary -- ch. 8. Practical exercises. Practical exercise 1. Practical exercise 2 Measuring Planck's constant.
Electronic reproduction.
Keywords: Physics -- Problems, exercises, etc; Physics -- Competitions; Electronic books